Exploring the experiences of women and people with diabetes in pregnancy in metropolitan and rural Australia: a national survey - Ellen Payne; Susan Heaney; Clare Collins; Megan Rollo; Leanne J. Brown (BMC Pregnancy and Childbirth)
Abstract Background Women and people diagnosed with diabetes in pregnancy, are recommended to have frequent monitoring and careful management for optimal pregnancy outcomes. This health care management should be supported by a multidisciplinary healthcare team. For individuals living in rural areas, there are increased barriers to healthcare access, with subsequent worse health outcomes compared to those in metropolitan regions. Despite this, there remains a lack of research into the experiences of healthcare delivery for rural women and people with diabetes in pregnancy. Methods Survey invitations were sent via the National Diabetes Services Scheme email list. The survey included multiple choice and open-ended questions. Responses from the open-ended question asking participants the changes they would want made to their care delivery were interpreted using qualitative content analysis. Responses were separated into metropolitan and rural categories using the Modified Monash Model criteria. Results There were 668 survey responses, with 409 responding to the open-ended qualitative survey question/s. 71.6% of respondents were metropolitan and 27.6% lived rurally. A total of 31 codes were established from the open-ended responses, with the five overarching themes of ‘quality of care’, ‘practice & communication’, ‘individual’s experience’, ‘access’ and ‘burden of care’ identified. The most frequently occurring codes irrespective of location included education or information (n = 45), frequency and timeliness of care (n = 42), no changes (n = 42) and improved health professional communication (n = 40). Local care options was the only code with more rural quotes compared to metropolitan. Conclusions The most frequently occurring codes had strong representation from metropolitan and rural respondents, indicating that those with previous diabetes in pregnancy had similar priorities for changes in their healthcare delivery regardless of location. Rural respondents identifying local care options as a priority for change is likely indicative of the rural healthcare landscape with limited access to care options. Recommendations from this study supported by previous research include focusing on improving health professional communication both with women and people with diabetes in pregnancy and with other relevant professionals. Recommendations for rural locations should focus on improving local care options whilst considering resource limitation, such as telehealth clinics.